Auricular Acupuncture at the "Shenmen" and "Point Zero" Points Induced Parasympathetic Activation. (4th June 2013) - Arai, Young-Chang P.; Sakakima, Yoshikazu; Kawanishi, Jun; Nishihara, Makoto; Ito, Akihiro; Tawada, Yusuke; Maruyama, Yuki
Abstract : Purpose . Since auricular acupuncture is a diagnostic and treatment system based on normalizing the body's dysfunction, auricular acupuncture has been applied for pain relief, relaxation, and so on. These techniques would modulate the autonomic nerve system, thereby inducing the above-mentioned effects. The aim was to see the effect of auricular acupuncture applied to the "Shenmen" and "Point Zero" points on the postoperative heart rate variability (HRV). Methods . Twenty-six patients who underwent hemicolectomy under general anesthesia were randomized into the control or the acupuncture group. After the operation and before emergence, the acupuncture group received auricular acupuncture. An electrocardiographic unit was placed for recording the autonomic nervous activities. Results . The low frequency (LF)/high frequency (HF) ratio of HRV increased (P = 0.0007 ) in the control, but the ratio in the acupuncture did not change. There were significant differences between the ratios of the two groups at 3 : 00, 4 : 00, and 5 : 00. HF of the acupuncture group tended to be higher. HFs of the acupuncture group were significantly higher than those of the control group at 3 : 00, 4 : 00, and 5 : 00. Conclusion . Auricular acupuncture kept the LF/HF ratio at lower levels and HF at higher levels during postoperative period in the patients who had undergone hemicolectomy.